A Fork in the Path: Developing Therapeutic Inroads with FoxO Proteins. Issue 3 (2009) - Maiese, Kenneth; Hou, Jinling; Chong, Zhao Zhong; Shang, Yan Chen
Abstract : Advances in clinical care for disorders involving any system of the body necessitates novel therapeutic strategies that can focus upon the modulation of cellular proliferation, metabolism, inflammation and longevity. In this respect, members of the mammalian forkhead transcription factors of the O class (FoxOs) that include FoxO1, FoxO3, FoxO4 and FoxO6 are increasingly being recognized as exciting prospects for multiple disorders. These transcription factors govern development, proliferation, survival and longevity during multiple cellular environments that can involve oxidative stress. Furthermore, these transcription factors are closely integrated with several novel signal transduction pathways, such as erythropoietin and Wnt proteins, that may influence the ability of FoxOs to act as a "double-edge sword" to sometimes promote cell survival, but at other times lead to cell injury. Here we discuss the fascinating but complex role of FoxOs during cellular injury and oxidative stress, progenitor cell development, fertility, angiogenesis, cardiovascular function, cellular metabolism and diabetes, cell longevity, immune surveillance and cancer.